2017
DOI: 10.1074/jbc.m116.766758
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits high glucose-induced NADPH oxidase 4 expression and matrix increase by recruiting inducible nitric oxide synthase in kidney proximal tubular epithelial cells

Abstract: High-glucose increases NADPH oxidase 4 (NOX4) expression, reactive oxygen species generation, and matrix protein synthesis by inhibiting AMP-activated protein kinase (AMPK) in renal cells. Because hydrogen sulfide (HS) inhibits high glucose-induced matrix protein increase by activating AMPK in renal cells, we examined whether HS inhibits high glucose-induced expression of NOX4 and matrix protein and whether HS and NO pathways are integrated. High glucose increased NOX4 expression and activity at 24 h in renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 55 publications
(56 reference statements)
1
30
0
Order By: Relevance
“…Resveratrol treatment in db/db mice prevented NOX4 expression primarily due to increased AMPK activity [132]. Similarly, numerous recent studies highlighted the beneficial effects of antioxidants or other compounds against renal injuries implicating AMPK/NOX4/ROS [133][134][135][136][137][138][139]. Furthermore, two independent studies reported that Sestrin-2 mediated activation of AMPK inhibits ROS production, podocyte impairment in the hyperglycemic condition, and suppresses NOX4 in glomerular mesangial cells [140,141].…”
Section: Ampk and Oxidative Stressmentioning
confidence: 95%
“…Resveratrol treatment in db/db mice prevented NOX4 expression primarily due to increased AMPK activity [132]. Similarly, numerous recent studies highlighted the beneficial effects of antioxidants or other compounds against renal injuries implicating AMPK/NOX4/ROS [133][134][135][136][137][138][139]. Furthermore, two independent studies reported that Sestrin-2 mediated activation of AMPK inhibits ROS production, podocyte impairment in the hyperglycemic condition, and suppresses NOX4 in glomerular mesangial cells [140,141].…”
Section: Ampk and Oxidative Stressmentioning
confidence: 95%
“…Moreover, the diabetic patients with dialysis exhibit reduced level of plasma H 2 S, and lower H 2 S level may contribute to uremic atherosclerosis in chronic hemodialysis patients with diabetic nephropathy [48]. Recent documents have demonstrated that renal H 2 S-producing enzymes CBS and CSE are downregulated in animals with type 1 or type 2 diabetes [45,49,50]. The above evidence indicates that H 2 S deficiency contributes to the development of diabetic kidney injury.…”
Section: Expression Of H2s In Diabetic Kidney Diseasementioning
confidence: 99%
“…Fakhruddin et al in 2017 affirmed that in a hyperglycemic state, NOX enzymes are activated directly or by way of impeding adenosine monophosphate-(AMP-) activated protein kinase [88]. Furthermore, in a hyperglycemic state, there is enhancement of NOX4 expression and oxidant production in the kidney [151], while Eid et al [152] and Lee et al [153] showed that in the same state, there is a subduing effect on AMPactivated protein kinase, thus bringing about the upregulation of NOX4 and ultimately promoting NOX activity in the glomerulus.…”
Section: Lipid Peroxidationmentioning
confidence: 99%